2016
DOI: 10.1108/f-04-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ethical codes implementation – a fuzzy approach

Abstract: Purpose Setting measurable criteria for implementing ethical codes is a pivotal issue in construction organizations. This paper aims to present an approach for evaluating ethical codes implementation within an organization based on 30 indicators for effective implementation of codes of ethics, with the objective of enhancing employees’ ethical behaviour within the organization. Design/methodology/approach This study builds on a theoretical model that was developed using existing classification in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…At this stage, convergent validity was determined by examining the measurement scale to see if all the items are loaded above the threshold value of 0.50 on their associated constructs, and if there is any cross-loading of items i.e. any item loading higher on other constructs more than the construct it supposed to measure (Hair et al , 2010; Ho and Oladinrin, 2016). The result of the preliminary analysis showed that one item (NWPI7) loaded below the threshold score (0.5), and was removed from the analysis.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…At this stage, convergent validity was determined by examining the measurement scale to see if all the items are loaded above the threshold value of 0.50 on their associated constructs, and if there is any cross-loading of items i.e. any item loading higher on other constructs more than the construct it supposed to measure (Hair et al , 2010; Ho and Oladinrin, 2016). The result of the preliminary analysis showed that one item (NWPI7) loaded below the threshold score (0.5), and was removed from the analysis.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Scholars have proposed various ideas of what the names of an ethical code are, ranging from code of ethics, code of conduct, business principles, corporate credo, code of practice and a value statement even though the most commonly used terms are "code of ethics" and "code of conduct" (Ho & Oladinrin, 2016). In terms of definitions, the code has been explained in many ways.…”
Section: Codes Of Ethicsmentioning
confidence: 99%
“…There are two common terms relating the management of a code of ethics namely, implementation and embeddedness. Code implementation describes the degree to which an organization put its efforts to make the code conveyed and its compliance ensured whereas code embeddedness refers to the extent to which the code is integrated into the culture of the organization (McCabe et al, 1996;Oladinrin & Ho, 2016). Therefore, the attitudes toward the code in this research referred the attitudes of the staff regarding the embeddedness and the implementation of the code in their institution.…”
Section: Hypothesesmentioning
confidence: 99%
“…Ho and Oladinrin [1]; Kaptein [2] show, a code of ethics is a basic element of the ethical infrastructure of an organization. Its acceptance covers the application of formal documents, in which the explicit declaration of the values that should steer the behaviour of employees and managers and support good practices and indicators related to the core of the organization, can be found.…”
Section: Introductionmentioning
confidence: 99%